Bilateral metabolic lesions in the basal ganglia: Case series and Literature review - Saquisela-Alburqueque, Victor V. (2023)
Introduction: Basal nuclei are gray matter substances, involved in the regulation of different metabolic functions and are vulnerable to situations of hypoxia and different pathological situations. Imaging findings are not specific in most cases. Case of report: The cases of ten patients with bilateral metabolic lesions in the basal nuclei treated at a national reference hospital in Peru are reported, and a review of the literature is carried out: 3 cases of postoperative hypoparathyroidism, 2 of Wernicke's encephalopathy, 1 with hepatolenticular degeneration, 1 with extrapontine myelinolysis, 1 methanol intoxication and 2 with hypoxic-ischemic encephalopathy. Conclusion: Bilateral lesions of the basal nuclei as a result of metabolic lesions are nonspecific, so the clinical context is of vital importance, as well as the particularities of the imaging findings, for the adequate recognition of the etiological entities and their timely management.